2004
DOI: 10.1590/s0100-879x2004000300021
|View full text |Cite
|
Sign up to set email alerts
|

The role of complement in the early phase of Leishmania (Leishmania) amazonensis infection in BALB/c mice

Abstract: Complement-depleted and -non-depleted BALB/c mice were inoculated with Leishmania (Leishmania) amazonensis promastigotes into the hind footpad to study the role of the complement system in cutaneous leishmaniasis. Total serum complement activity was measured by hemolytic assay and C3 fragment deposit at the inoculation site was determined by direct immunofluorescence in the early period of infection, i.e., at 3, 24, 48 h and 7 days post-infection. The inflammatory reaction and the parasite burden were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
7
1
3
Order By: Relevance
“…Consequently, in vivo , parasite trapping to pyroptotic debris may favor parasite spreading - as shown for other forms of host cell death – allowing for stealthy phagocytosis by freshly recruited macrophages in the inflammatory infection site (de Menezes et al, 2016). On the other hand, the extracellular exposure of amastigotes could expose parasites to complement-dependent cytotoxicity that is known to control parasite load in vivo (Laurenti et al, 2004), or to anti-leishmanial antibodies that could promote cell-mediated cytotoxicity via Fc receptor-dependent phagocytosis. Our results will stimulate future studies designed to assess the role of macrophage pyroptosis in Leishmania dissemination, transmission, and immune-pathology.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, in vivo , parasite trapping to pyroptotic debris may favor parasite spreading - as shown for other forms of host cell death – allowing for stealthy phagocytosis by freshly recruited macrophages in the inflammatory infection site (de Menezes et al, 2016). On the other hand, the extracellular exposure of amastigotes could expose parasites to complement-dependent cytotoxicity that is known to control parasite load in vivo (Laurenti et al, 2004), or to anti-leishmanial antibodies that could promote cell-mediated cytotoxicity via Fc receptor-dependent phagocytosis. Our results will stimulate future studies designed to assess the role of macrophage pyroptosis in Leishmania dissemination, transmission, and immune-pathology.…”
Section: Resultsmentioning
confidence: 99%
“…While in vivo study of C5‐deficient mice showed no role for complement in controlling L . major infection in vivo (Spath et al ., 2003a), a separate study that depleted the whole complement system in BALB/c mice using cobra‐venom anti‐complement protein challenge showed a profound role for complement in controlling L. amazonensis infection in vivo (Laurenti et al ., ). Thus, comprehensive in vivo studies with Leishmania infections of mice lacking individual components of complement (C3b –/– , C5b –/– , C5a –/– etc.)…”
Section: Perspectives and Conclusionmentioning
confidence: 97%
“…14 We applied the same model to study the effect of thymulin 5cH in a parasitic experimental model, using Leishmania (L.) amazonensis infection. The idea to perform this study is based on the fact that this parasite causes very particular mechanisms of interaction with its host, modifying both natural and acquired immune responses, [14][15][16] including the phagocyte activity in the destruction of amastigote forms. 16,17 The aim of this study is to analyze the putative immune modulation mechanisms of thymulin 5cH treatment in the experimental infection with Leishmania (L.) amazonensis in mice, by using specific markers to recognize some immune cells involved in the local and systemic hostparasite interactions.…”
Section: Introductionmentioning
confidence: 99%